Retrograde Jejunogastric Intussusception (RJGI): A Life- Threatening Complication after Gastric Bypass Surgery - Faruk, Imtiaz; Kabir, Sheikh Firoj; Alam, Syed Mahbubul; Hasan, Kh ABM Abdullah Al (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Retrograde jejunogastric intussusception (RJGI) after gastric bypass surgery is a rare but potentially life threatening complication. This complication may develop after simple gastrojejunostomy, after lower partial resection of stomach with gastrojejunostomy (Billroth-II gastric surgery) or after Roux-en-Y gastric bypass. Among the three anatomic type of jejunogastric intussusception (JGI), type-II is the commonest variety. The acute form is a surgical emergency. Mortality rate is very high. Little is known about the mechanism but many literatures indicate abnormal motility may be a cause. A 50 year old male presented to us with a three month history of repeated vomiting and one day of upper mid-abdominal pain. He had a history of gastric bypass for pyloric stenosis 12 years back. Diagnosis was confirmed by upper GI endoscopy. At laparotomy type II retrograde jejunogastric intussusception was identified. En-block resection of affected segment of jejunum and lower part of the stomach was done followed by Roux-en-Y reconstruction. RJGI is a rare complication of gastric bypass surgery. Early diagnosis is imperative. High index of suspicion is therefore important. Barium meal X-ray, ultra sonogram, enhanced CT scan occasionally be diagnostic, but endoscopy is certainly diagnostic in experienced hand. Laparotomy is mandatory. Surgical options include simple reduction, en-block resection and/or plication. J Bangladesh Coll Phys Surg 2015; 33(3): 161-165